2017
DOI: 10.15406/apar.2017.06.00223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation with Different Levels of Saline Water Type on Husk Tomato Productivity

Abstract: This investigation was carried out in a private farm located at Shebeen El-Qanatir city, El-Qaliubiya governorate, Egypt during the two successive seasons (2011/2012 and 2012/2013 A.D.) to study the response of husk tomato plants (Physalispubescens L.) cv. (local variety) to different levels of saline water. To test the growth ability of salt tolerance with best fruit yield and their quality under saline condition. Plants was irrigated with salty water with concentration of 2000, 4000, 6000 and 8000ppm. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…These results are consistent with Zhang et al [16], who reported that adding an amount of salt to the nutrient solution improves the quality of tomato fruits. The same was reported by Helaly et al [19], who reported that irrigating tomatoes with saline water resulted in a significant increase in total soluble solids and improved fruit quality, compared to the control. Although total tomato fruit production decreased with increasing irrigation water salinity, internal quality, characterized by taste and health-promoting compounds, such as total soluble solids and organic acids in tomato fruits, can be improved [18].…”
Section: Salinity Levelsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are consistent with Zhang et al [16], who reported that adding an amount of salt to the nutrient solution improves the quality of tomato fruits. The same was reported by Helaly et al [19], who reported that irrigating tomatoes with saline water resulted in a significant increase in total soluble solids and improved fruit quality, compared to the control. Although total tomato fruit production decreased with increasing irrigation water salinity, internal quality, characterized by taste and health-promoting compounds, such as total soluble solids and organic acids in tomato fruits, can be improved [18].…”
Section: Salinity Levelsupporting
confidence: 84%
“…Also, Zaki et al [17] reported that increasing salinity levels gradually decreased average tomato fruit weight. Helaly et al [19] stated that irrigating tomatoes with saline water resulted in a decreased fruit yield, compared to the control. In general, increasing salt concentration in the nutrient solution led to a decrease in fruit yield.…”
Section: Salinity Levelmentioning
confidence: 99%
“…In contrast, the other genotypes did not change their fruit number under salinity stress conditions (Table 1). This decline in fruit number can be attributed to the disruption of the plant's physiological functions caused by osmotic stress and the consequent imbalance of nutrients resulting from the increased concentration of salt [38]. Therefore, our results indicate that the decline in production was primarily driven by a decrease in the average fresh fruit weight and the number of fruits per plant [39], and this effect was genotype-dependent.…”
Section: Discussionmentioning
confidence: 65%
“…11,12 Consequently, salinity-induced challenges remain a central concern for global tomato cultivation and fruit quality. It was reported that although tomato fruit yield productivity decreased with saline water irrigation, fruit quality increased based on the increased concentrations of β-carotene, lycopene, and vitamin C. 13 Yet, research on amino acids and many other important phytochemicals, including carotenoids, and specific polyphenols like flavonoids, flavanones, and flavones, remains limited for tomatoes. 14−16 Targeted and untargeted metabolite analysis has been applied to understand variations during different growth stages, plant's metabolic response to environmental contaminants, the impacts of soil types, and the effect of abiotic and biotic stresses.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is estimated that more than 10,000 tomato cultivars have been developed to improve the quality and taste of tomatoes in terms of flavors, nutrients, and appearance. , Most tomato varieties are sensitive to salt, leading to notable decreases in their growth and productivity worldwide due to elevated soil salinity levels, but the impact of salinity on the quality of the crop has not been sufficiently investigated. , Consequently, salinity-induced challenges remain a central concern for global tomato cultivation and fruit quality. It was reported that although tomato fruit yield productivity decreased with saline water irrigation, fruit quality increased based on the increased concentrations of β-carotene, lycopene, and vitamin C . Yet, research on amino acids and many other important phytochemicals, including carotenoids, and specific polyphenols like flavonoids, flavanones, and flavones, remains limited for tomatoes. …”
Section: Introductionmentioning
confidence: 99%